α-synuclein genetic variability: A biomarker for dementia in Parkinson disease - Guella, I; Evans, D; Szu-Tu, C; Nosova, E; Bortnick, S; Goldman, J; Dalrymple-Alford, J; Geurtsen, G; Litvan, I; Ross, O; Middleton, L; Parkkinen, L; et al. (Wiley, 2016)
Objective The relationship between Parkinson disease (PD), PD with dementia (PDD), and dementia with Lewy bodies (DLB) has long been debated. Although PD is primarily considered a motor disorder, cognitive impairment is often present at diagnosis, and only ∼20% of patients remain cognitively intact in the long term. Alpha-synuclein (SNCA) was first implicated in the pathogenesis of the disease when point mutations and locus multiplications were identified in familial parkinsonism with dementia. In worldwide populations, SNCA genetic variability remains the most reproducible risk factor for idiopathic PD. However, few investigators have looked at SNCA variability in terms of cognitive outcomes. Methods We have used targeted high-throughput sequencing to characterize the 135kb SNCA locus in a large multinational cohort of patients with PD, PDD, and DLB and healthy controls. Results An analysis of 43 tagging single nucleotide polymorphisms across the SNCA locus shows 2 distinct association profiles for symptoms of parkinsonism and/or dementia, respectively, toward the 3′ or the 5′ of the SNCA gene. In addition, we define a specific haplotype in intron 4 that is directly associated with PDD. The PDD risk haplotype has been interrogated at single nucleotide resolution and is uniquely tagged by an expanded TTTCn repeat. Interpretation Our data show that PD, PDD, and DLB, rather than a disease continuum, have distinct genetic etiologies albeit within one genomic locus. Such results may serve as prognostic biomarkers to these disorders, to inform physicians and patients, and to assist in the design and stratification of clinical trials aimed at disease modification. Ann Neurol 2016;79:991–999